Families, Children and the Development of Dysfunction. - Dadds, Mark R. (Developmental clinical psychology and psychiatry., 1994)
The family plays a central role in the mental health of children. This study of the family in relation to child development and dysfunction explores whether there are critical family characteristics that are reliably predictive of childhood dysfunction - and whether these characteristics can be modified by family therapy. The author places specific types of dysfunction such as depression, conduct problems and anxiety in the context of family influences, and details issues of identification, assessment and treatment of childhood dysfunction in relation to family processes.